Comparison of cell viability, cytomorphometric and periodontal index of human oral mucosal cell exposed to two conventional fixed orthodontic appliances - Almashharawi, Rami K.M. (2018)
The corrosive environment of the oral cavity is a major cause of concern during the use of orthodontic appliances. The reasons are because fixed orthodontic appliances are made from different alloys materials. Exposure of soft tissues to these materials while using the appliances may lead to some chemical reactions due to material degradation which may release certain type of ions. The study aims to analyse the cell viability changes, and cytomorphometric alterations in the nuclear area (NA), cytoplasmic area (CA), and nuclear-cytoplasmic ratio (N/C) of the human buccal mucosa of patients treated with metallic and ceramic orthodontic appliances respectively. The study was also carried out to assess the periodontal health of patients under those orthodontic treatments. In this study, twenty-six subjects who were orthodontic patients attending Dental Clinic at Hospital Universiti Sains Malaysia were recruited. The subjects were divided into two groups; one group was treated with metallic appliances (n=13), while another was treated with ceramic appliances (n=13). The buccal swab was taken from each participant three times, prior to treatment (baseline), at 3-month post-treatment, and then at 6-month posttreatment. To examine the periodontal health of patients, four periodontal parameters were assessed at the same time points; plaque index (PI), bleeding on probing (BOP), periodontal pocket depth (PPD) and clinical attachment loss (CAL). Cell viability of the oral buccal mucosa was evaluated using Trypan blue staining, followed by lightmicroscopy analysis. For cytomorphometry, the cells were stained using Papanicolaou stain, followed by an assessment using ImageJ software. All data were subjected to statistical analysis. At 3-month both metallic (56.01±SE1.69, p ≤ 0.05) and ceramic (64.41±SE 1.34, p ≤ 0.05) groups showed a significant decrease in the cellular viability respectively in comparison to the baseline group. Cytomorphometry analysis of the buccal mucosa cells at 3-month showed a significant decrease of NA in both metallic (45.5±SE 0.94, p ≤ 0.05) and ceramic (55.2±SE 0.63, p ≤ 0.05) groups. The N/C ratio was (30.1±SE 1.02, p ≤ 0.05) for metallic, while ceramic was (41.1±SE 0.92, p ≤ 0.05). The analysis showed that there was an increase in CA of metallic (125.1±SE 1.22, p ≤ 0.05) in comparison to ceramic (118.3±SE 1.16, p ≤ 0.05). PI analysis showed a significant increased at 3-month in both metallic (1.98±SD0.39, p ≤ 0.05) and ceramic groups (1.7±SD0.45, p ≤ 0.05). Similarly, BOP showed a significant increased at 3-month in both metallic (0.30±SD0.09, p ≤ 0.05) and ceramic groups (0.20±SD0.08, p ≤ 0.05). PPD showed no significant difference at 3-month in both metallic (1.88±SD0.61, p ≥ 0.05) and ceramic group (1.86±SD0.60, p ≥ 0.05), similar to CAL, in which the metallic group is (1.99 ±SD0.72, p ≥ 0.05) and the ceramic group is (1.98±SD0.87, p ≥ 0.05). However, all investigated variables and parameters have no significant difference at 6-month in comparison to the baseline group. Fixed metallic and ceramic orthodontic appliances can induce cytotoxicity to the buccal mucosa cells, changes in cellular morphology and affects periodontal health at 3-month after the orthodontic treatment. These changes were more prominent in the metallic group, while all changes at 6-month showed no significant difference which indicates cells tolerance for healing. Both metallic and ceramic appliances are considered biocompatible. Using ceramic appliances being more advantageous.